Comportamiento epidemiológico temporo espacial relacionado a intoxicaciones por plaguicidas en Ecuador del periodo 2018 al 2021 - Jaramillo Gonzalez, Jhordan Stalyn (2024)
Pesticide poisoning is a type of poisoning that occurs due to exposure to toxic chemicals used to control pests, such as insects, rodents, weeds and fungi. Characteristic symptoms include nausea, vomiting, diarrhea, abdominal pain, dizziness, headache, weakness, difficulty breathing, skin and eye irritation, and seizures, Diagnosis in based on the evaluation of clinical symptoms and a history of pesticide exposure. To prevent such poisonings, the use of personal protective equipment (PPE) is essential. The objective of this study was to determine the epidemiological patterns of pesticide poisonings by age, sex and region in the Coastal, Andean and Amazon areas of Ecuador from 2028 to 2021, with the purpose of proposing an educational strategy for prevention. This was an analytical study with a mixed-methods, cross-sectional cohort approach, based on a population of 5225 cases obtained from data from the National Institute of Statistics and Census (by its Spanish acronym INEC). Results showed that the majority of cases occurred in men with 59.1%, predominantly in the 20-39 age group with 44.5%, and the region with the highest number of poisonings was the Coast with 40.6%. In terms of proportional trends, there was a notable decrease in cases over time. In the Coastal region, cases decreased from 11.92% in 2018 to 7.54% in 2021, in the Andean region form 9,68% to 7.94%, and in the Amazonian region from 7,14% to 6,35%. In Ecuador, recent years have shown a downward trend in pesticide poisoning cases, with slight fluctuations, likely due to increased awareness of the risks associated with pesticide use and the probable appropriate use of personal protective equipment